INTERPRETING LEARNING DIFFICULTIES THROUGH THE THEORY OF MULTIPLE INTELLIGENCES AND THE THEORY OF EMOTIONAL INTELLIGENCE - FLORENTIN REMUS MOGONEA (Studia Universitatis Babes-Bolyai, 2010)
ABSTRACT. In opposition with classical theoretical approaches regarding human intelligence (often defined as that capacity, ability to adapt to the environment, adaptation that occurs in two stages- assimilation-adjustment), at present we witness an increase frequency of the theories that don't regard intelligence as a monolithic, uni-composite structure. Thus, people are talking about a triarchic structure of the intelligence (Sternberg) or of emotional intelligence (Goleman), and even of social intelligence. In the same category of approaches we find H. Gardner's theory of multiple intelligences which starts from the idea that some children with high intelligence quotient can have not very good results at school, being considered "smart" only those who have good results at the intelligence tests. The school success is no longer guaranteed by the positive educational valorification of a high intelligence quotient (Intelligence Quotient-IQ), but also by the presence, the valorization and the development of emotional intelligence (Emotional Intelligence Quotient-EQ) and of social one (Social Intelligence Quotient-SQ).